Ab initio study of high tridymite by the formalism generator coordinate Hartree-Fock - Jardim, I. N.; Treu, O.; Martines, MAU; Davolos, Marian Rosaly [UNESP]; Jafelicci, M.; Pinheiro, J. C. (Elsevier B.V., 1999)
The Generator Coordinate Hartree-Fock (GCHF) Method is applied to generate extended 14s 8p and 17s 11p Gaussian basis sets for the atoms O and Si, respectively. The role of the weight functions in the assessment of the numerical integration range of the GCHF is shown. The Gaussian basis sets are contracted to [6s4p] O atom and [8s5p] Si atom by the Dunning's segmented contraction scheme. To evaluate the quality of our contracted [6s4p] and [8s5p] bases in molecular calculations we accomplish calculations of total and orbital energies in the Hartree-Fock-Roothaan method for O-2 and SiO molecules. We compare the results obtained with the our (14s 8p) and (17s 11p) bases sets with the of 6-311G basis and with values from the literature. The addition of one d polarization function in the silicon basis and its utilization with the basis for oxygen leads to the calculation of electronic properties and IR Spectrum of high tridymite in space group D-3d. (C) 1999 Elsevier B.V. B.V. All rights reserved.
Keywords: electronic properties of high tridymite; IR Spectrum of high tridymite; generator coordinate HF method